jdaai 2022
DOI: 10.46632/jdaai/1/2/5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Performance of Micro and Small Entrepreneurs by (COPRAS)

Abstract: Micro and Small Entrepreneurs Micro-entrepreneurs, those who own and operate businesses with fewer than five employees, are the most common type of entrepreneurs in the world and make up a large part of the informal economy in low-income countries. Micro and Small Entrepreneurs of the proposed method Comparative analysis to illustrate the application Conducting and credit evaluation Example is used. COPRAS (Complex Proportional Evaluation is proposed to evaluate the possible maintenance strategy. Linguistic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The findings indicated that tempering at T6 and T7 temperatures for 250 minutes produced the highest resistant to stress corrosion cracking (SCC). However, samples that had been annealed for 8 minutes at 200°C showed decreased resistance to stress corrosion cracking [7]. The results of the electrochemical tests showed the fact that the PEO covering increased corrosion resistance, but that it had no effect on SCC protection within the ASTM D1384 solution used for the sample.…”
Section: Stress Corrosion Crackingmentioning
confidence: 97%
“…The findings indicated that tempering at T6 and T7 temperatures for 250 minutes produced the highest resistant to stress corrosion cracking (SCC). However, samples that had been annealed for 8 minutes at 200°C showed decreased resistance to stress corrosion cracking [7]. The results of the electrochemical tests showed the fact that the PEO covering increased corrosion resistance, but that it had no effect on SCC protection within the ASTM D1384 solution used for the sample.…”
Section: Stress Corrosion Crackingmentioning
confidence: 97%
“…Of rural electrification in developing countries as a driver, climate change solar photovoltaic (PV) as a contributor to reduction advances in technology, PV efficiency and improve scalability innovations poverty and greenness significant in reducing greenhouse gas emissions suggests that improvements can be made. Global access to solar resources and costs of PV due to innovation drive accelerate sustainable growth by decreasing pathway to renewable energy sources provides open-source software development less than proprietary software cost-effective and innovative demonstrated computer code generation [5]. Solar photovoltaic technologies, environment and to solve energy problems surveys should be conducted and the PV life cycle is from cradle to grave takes mechanism, which in extracting raw materials removing sunlight from or as far as recycling.…”
Section: Introductionmentioning
confidence: 99%